2020
DOI: 10.1016/j.heliyon.2020.e04396
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents, usage and pharmacological activity of Cassia alata

Abstract: Cassia alata or locally known as Ketepeng Cina (Indonesia) and Gelenggang (Malaysia) has been used as a traditional medicine to treat various diseases, especially skin diseases. In addition, C. alata has been reported to have potential anti allergic, anti inflammatory, antioxidant, anticancer, antidiabetic, and antifungal. Metabolite compounds that have been isolated from C. alata include flavones, flavonols, flavonoids glycosides, alatinon, alanonal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…Based on the results of the study, it was found that the use of C. alata leaf extract could increase egg hatchability and survival of P. hypophthalmus (Table 1), where the higher the dose of extract used in the treatment will also increase the hatchability of fish eggs. Fatmawati et al [6] stated that C. alata leaf extract contains chemical compounds that can be used as antimicrobials. Furthermore, Makinde et al [12] said that the antibacterial and antifungal activity of the aqueous and methanolic extracts of C. alata leaves found that they had more antifungal properties than antibacterial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the study, it was found that the use of C. alata leaf extract could increase egg hatchability and survival of P. hypophthalmus (Table 1), where the higher the dose of extract used in the treatment will also increase the hatchability of fish eggs. Fatmawati et al [6] stated that C. alata leaf extract contains chemical compounds that can be used as antimicrobials. Furthermore, Makinde et al [12] said that the antibacterial and antifungal activity of the aqueous and methanolic extracts of C. alata leaves found that they had more antifungal properties than antibacterial.…”
Section: Resultsmentioning
confidence: 99%
“…One of the natural ingredients that has the potential to inhibit the growth of pathogens in fish is the use of Cassia alata leaves. This plant is known by different names in different countries, namely as Gelenggang (Malaysia), Ketepeng Badak or Ketepeng Cina (Indonesia) and bush ringworm (Australia) and has been used as as traditional medicine to treat various diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening for secondary metabolites in the hydro-ethanolic extract of SP leaves was performed using standard phytochemical methods reported in the literature. 10 11 Results suggested that alkaloid, saponin, tannin, cardiac glycoside, flavonoid, anthraquinone, and phenol were present in the SP extract, while steroids were absent. Tannins, flavonoids, and phenols are potent antioxidants, and antioxidants have been implicated in wound healings by improving vascularization and reducing lipid peroxidation which in turn prevents necrosis of cells and promotes cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of alkaloids, saponins, tannins, steroids, cardiac-active glycoside, flavonoids, anthraquinones, and phenols in the extract was assessed respectively as the following according to the reported studies 10,11 :…”
Section: Phytochemical Screening Of Plant Extractmentioning
confidence: 99%
“…The antifungal activity of P. thonningii against C. albicans was studied previously with the ethanolic extract showing significant activity in inhibiting the growth of cells and an MIC of 0.312 μ g/mL. Other studies [ 38 , 39 ] have found that the ethanol leaf extract of Cassia alata caused a dose-dependent effect on Candida albicans , Microsporum canis, and Trichophyton mentagrophyte . The phytochemical and antifungal analysis of the ethanolic extract of P. thonningii showed the presence of flavonoids which were effective in inhibiting the growth of C. albicans , Colletotrichum musae, and Sclerotium rolfsii [ 40 42 ].…”
Section: Resultsmentioning
confidence: 99%